Ageing and seasonal effects on amorphous silicon photovoltaic modules in a Mediterranean climate. (March 2022) - Mateo, C.; Hernández-Fenollosa, M.A.; Montero, Á.; Seguí-Chilet, S.
Abstract: This contribution presents a field study in which the long-term behaviour of two a−Si photovoltaic plants is studied. Two grid-connected a−Si:H photovoltaic plants located in Valencia (Spain) have been monitored during their first eight years of operation under real outdoor conditions. A per-unit approach and an STC normalisation have been made to analyse and compare photovoltaic plants with differences in electrical characteristics. An averaging process of the filtered and normalised data produces a monthly averaged value that is used to evaluate the ageing and seasonal effects experienced by the two photovoltaic plants. An analysis of the variations in the per unit output power finds that a seasonal effect is superimposed on the long-term stabilisation process. The study concludes that the long-term average stabilisation factor is equal to 1, 35% per year, with a seasonal effect that shows a sinusoidal variation with an average amplitude of the sinusoidal oscillation equal to 2, 71% per year. An estimation of the energy yield is performed considering the different ageing approaches presented in the study. Using the factors obtained from the experimental values, the ageing and seasonal effects are modelized, and a linear and an exponential expression is proposed to fit the long-term behaviour of both a−Si photovoltaic plants. Results obtained with the statistical analysis are compared with the experimental data and it is found that the exponential behaviour matches the experimental values. Graphical abstract: Image 1 Highlights: Long-term variations in PV efficiency in a−Si:H modules. Ageing and seasonal effects in a−Si:H modules. Linear and exponential expressions for a long-term fitting model of PV behaviour.